Tackling Workforce Constraints : For Dignified, Person-Centered Care Amidst Demographic Change - World Bank Group (World Bank, Washington, DC, 2019)
Wealthy countries are aging rapidly, driving higher usage of health services. Most members countries in the Organisation for Economic Co-operation and Development (OECD) have expanded medical education to proactively address growing demand, rapidly expanding their health workforce over the last two decades. Nonetheless, their health systems are struggling to direct newly trained physicians and nurses to frontline specialties in general practice, family medicine, and geriatrics where they are needed most. Exacerbating the challenge, demographic change is happening in a context where lower pay and perceived lack of prestige deter entry into primary care specialties, creating chronic physician shortages on the frontline. To respond to demographic transformation and longstanding primary care deficits, mature health systems will need to incentivize entry into frontline specialties and better prioritize physicians' scarce time.